Developing of Teaching Modules with PBL-STEM Model of Photosynthesis Material to Increase Critical Thinking Skills of Grade IV Elementary School Students - Mardita, Meza; Haryani, Sri; Rengga, Wara Dyah Pita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2024)
This study aims to develop teaching modules with PBL-STEM models on photosynthesis material. This research is a research and development using the ADDIE (Analysis, Design, Develop, Implementation and Evaluate) development model developed by Raiser and Mollenda in the 1990s. The research and development involved two experts as validators. The data collection technique in this study was a validity questionnaire and a practicality questionnaire. The results of the media validity test on the aspects of cover design and module content design obtained a percentage of 88.4% with a very valid category. While the results of material expert validation which includes aspects of content feasibility, linguistic feasibility, presentation and self-study obtained a percentage of 100% with a very valid category. For the practicality assessment, the teacher and student responses showed that the product developed was very practical with a percentage score of 85.4% and 98.7% respectively. From the results of validity and practicality, it can be concluded that the teaching module with the PBL-STEM model of photosynthesis material can be declared valid and practical and is suitable for testing. This research is expected to help educators in developing teaching modules, especially in science subjects and can be a reference for other researchers